The Role Of Bakorwil III As a Government Organizer in Inter-Regional Cooperation in Greater Malang Tourism Management - Hafids Sutatak; Fedianty Augustinah; Ika Devy Pramudiana; Sri Kamariyah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to describe and analyze the role of Bakorwil III as a government organizer in inter-regional cooperation for tourism management in Malang Raya, as well as the obstacles faced by Bakorwil III. The research method used is qualitative descriptive, with data collection techniques including interviews, observations, and documentation. The research informant is the Head of the Coordinating Agency for Region III Malang. The data analysis technique uses the interactive model developed by Miles et al. (2014), which includes data condensation, data presentation, and drawing conclusions. The results show that Bakorwil III Malang, as a representative of the East Java Provincial Government, has the main task of coordinating inter-regional cooperation in tourism management in Malang Raya. Bakorwil III Malang ensures that every stage of the cooperation formation process, from planning to the signing of agreements, is carried out. As a facilitator, Bakorwil III Malang coordinates between the Malang Raya government and other stakeholders. Bakorwil III also facilitates information related to Government Regulation No. 28 of 2018 regarding Regional Cooperation. The obstacles faced by Bakorwil III in carrying out its role include differences in political interests, development disparities, regional characteristic differences, and budget limitations.